Pharmacological treament approachs for parkinson's disease today and in the future - ARICIOĞLU, FEYZA (MARMARA UNIV, INST HEALTH SCIENCES, 2015)
Parkinson's disease, a chronic progressive neurodegenerative disorder induced by loss of dopaminergic neurons in the nigrostriatal pathway, is characterized by bradykinesia, rigidity, tremor and postural instability. Parkinson's disease affects 5 million people and it is the second most common neurodegenerative disease worldwide. Currently available treatments are not intended to change the neurodegenerative process but with the aid of symptomatic treatments patients' quality of life will be improved. Although levodopa is the most effective drug in the treatment of the motor symptoms of Parkinson's disease, it leads to dyskinesias and motor fluctuations. Thus, levodopa dosage has to be changed or new drugs (e.g., dopamine agonists, catechol-O-methyltransferase inhibitors, monoamine oxidase type B inhibitors) must be added to the treatment of Parkinson's disease. Therefore, it has been started to develop new therapeutic approaches as an alternative to conventional therapies. These approaches are currently treating dyskinesias and motor fluctuations symptomatically. On the other hand treatment with neurotrophic factors and cell transplantation belong to the restorative approaches, which are almost at the beginning of investigation. Symptomatic treatment approaches are deep brain stimulation; subcutaneous apomorphine; carbidopa/levodopa intestinal gel; the Accordion Pill; extended-release amantadine; adenosine receptor antagonists; metabotropic glutamate receptor antagonists and gene therapy. Some of these approaches have recently been used, while others are still being investigated. All of these approaches have been a new hope for Parkinson's disease patients.
Keywords: Parkinson's disease; treatment; psychopharmacology